Pendidikan Humanis dalam Pandangan Paulo Freire - Abdul Rasyid (EKSPOSE, 2018)
Humanistic education in the perspective of Paulo Freire teaches about position of educational process as a social transformation. Hence, providing humanistic society relates closely to the humanistic education. The perspective of Paulo Freire towards humanistic was influenced his social background that did not appreciate the humanistic values so that he tried to accelerate humanistic education through humanistic education.